PENGEMBANGAN FILM DOKUMENTER PEMBUATAN SELAI KELAPA PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Reza, Muhammad; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Universitas Tanjungpura, 2023)
Teachers had difficulty when teaching submaterial the plant roles in the economic sector due to limited time and teaching aids. This study aimed to determined the feasibility of documentary films as an alternative learning media in the submaterial of the plant roles in the economic sector. The research was conducted from September 2021 to March 2022 with a descriptive method. The documentary film was validated by five validators, including two biology education lecturers from FKIP Untan, two biology teachers for class X SMA, and one film editor from Wahana Kreator Jakarta. Validation contains of seven aspects, namely format, content, language, cohesiveness and balance, audio, image, and usability with several criteria in each aspect. The validation data was then analyzed by used Content Validity Ratio (CVR) analysis. The results of the validation data analysis resulted in a CVR value of 1.00 with a valid category. Therefore, the documentary film can be declared valid and suitable to be used as an alternative learning media on the submaterial of the plant roles in the economic sector.